Pharmacological Correction of Cardiovascular Complications After Anthracycline-Based Therapy for Acute Leukemias (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study investigated the efficacy of medicinal correction strategies in mitigating cardiovascular complications induced by anthracycline therapy in patients diagnosed with acute leukemias. A retrospective cohort of 150 adult patients, treated with anthracycline-based chemotherapy between January 2015 and December 2025, who subsequently developed cardiac dysfunction (LVEF